Fatigue Crack Growth Failure and Lifing Analyses for Metallic Aircraft Structures and Components - Wanhill, Russell; Barter, Simon; Molent, Loris; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2019)
This book provides a concise discussion of fatigue crack growth (FCG) failure and lifing analysis methods for metallic aircraft structures and components. After a reasonably concise historical review, surveys are made of (i) the importance of fatigue for aircraft structural failures and the sources of fatigue nucleation and cracking, (ii) contemporary FCG lifing methods, and (iii) the Quantitative Fractography (QF) required for determining the actual FCG behaviour. These surveys are followed by the main part of the book, which is a discussion, using case histories, of the applicabilities of Linear Elastic Fracture Mechanics (LEFM) and non-LEFM methods for analysing service fatigue failures and full- and sub-scale test results. This discussion is derived primarily from the experiences of the Defence Science and Technology Group in Melbourne, Australia, and the Netherlands Aerospace Centre, Marknesse, the Netherlands.
1 Historical Review -- 1.1 FCG Parameters, Concepts and Testing -- 1.2 FCG 'Laws' and Models -- 1.3 Summary -- 2 Basic Information for Aircraft FCG Failure and Lifing Analyses -- 2.1 Importance of Fatigue for Aircraft Structural Failures -- 2.2 Fatigue Crack Nucleation, Discontinuities, Early FCG and Damage Tolerance -- 2.3 Summary of FCG Lifing Methods -- 3 Quantitative Fractography (QF) for FCG analyses -- 3.1 Introduction -- 3.2 Fatigue Striation FCG Analyses -- 3.3 Progression Marking FCG Analyses -- 3.4 Fatigue-nucleating Discontinuities and Equivalent Pre-crack Sizes (EPS) -- 3.5 QF Techniques for Fatigue Fracture Surfaces -- 3.6 A Cautionary Note -- 4 Aermacchi MB-326H Wing Spar (1990): Exponential FCG Analysis -- 4.1 Introduction -- 4.2 FCG Analysis for the Failed Spar -- 4.3 Further Examination of Wing Spars -- 4.4 Lessons Learned -- 5 P&W 125B Engine Bearing (1994): 2-Stage Exponential FCG Analysis -- 5.1 Introduction -- 5.2 The Failed No.3 Bearing: Macroscopic and /Metallographic Examination -- 5.3 Cage Failure and FCG Analysis -- 5.4 Interpretation of the Results, Conclusions, and Remedial Action -- 6. EBA Example Lifing Assessment (2004): F/A-18 Horizontal StabilatorSpindles -- 6.1 Introduction -- 6.2 EBA Validation for the F/A-18 Horizontal Stabilator Spindles -- 6.3 EBA and Total Life Assessment for the F/A-18 Horizontal Stabilator Spindles -- 7. LCFLF Example Lifing Assessment (2004): F/A-18 Vertical Tail Attachment Stubs -- 7.1 Introduction -- 7.2 The FT46 Stub Flange Crack -- 7.3 Fractography of the FT46 Stub Flange Crack -- 7.4 LCFLF Life Assessment for the FT46 Stub Flange Crack -- 8. Cubic Rule Life Prediction Examples -- 8.1 Introduction -- 8.2 McDonnell Douglas F4E Spectrum Coupon Test Data -- 8.3 Lockheed Martin P3C Spectrum Coupon Test Data -- 8.4 Summary -- 9. Fokker 100 Fuselage Test: Lap Joints Exponential FCG Analysis -- 9.1 Introduction -- 9.2 FCG Analysis of the Cracked Lap Splice [71.72.95] -- 10. Sikorsky S-61N Rotor Blade (1974): Exponential FCGR Analysis -- 10.1 Introduction -- 10.2 FCG Analysis for the Crashed Helicopter -- 10.3 Prediction of Detectable FCG Lives -- 10.4 Results and Remedial Actions (Lessons Learned) -- 11. Westland Lynx Rotor Hub (1998): Progression Marking LEFM Analysis -- 11.1 Introduction -- 11.2 Fractography of Early Fatigue Cracking in the M326 Yellow Arm -- 11.3 Fractography of Early Fatigue Cracking in the M6 Arm and M326Specimens -- 11.4 FRTB + LEFM Estimations of Damaging Service Fatigue Stress Levels -- 11.5 Measurements of Service Loads and Fatigue Analysis by GKNW -- 11.6 Causes of Failure and Remedial Action -- 12. Closing Remarks -- References.
Keywords: Aerospace engineering; Astronautics; Mechanics, Applied; Solids; Building materials; Aerospace Technology and Astronautics; Solid Mechanics; Structural Materials